Next generation of radio spectrum management licensed shared access and the trade-off between static and dynamic efficiency - Maria Massaro; Gérard Pogorel (International Telecommunications Society (ITS), 2015)
Increasing demand for access to the radio spectrum is setting the stage for a revision of existing radio spectrum management practices. A new wave of spectrum policy reforms can be envisaged, with a potential shift of policy focus from static to dynamic efficiency. This might translate into a new generation of radio spectrum management tools more centred on spectrum sharing solutions. Spectrum sharing could ensure more flexibility in spectrum use and certainty of radio spectrum access, which might eventually encourage investment and innovation, i.e. dynamic efficiency. Among several forms of spectrum sharing, the concept of Licensed Shared Access has recently been under scrutiny, in particular in the European Union and in the United States. Against this background, this paper is intended as a progress report on the discussion upon the LSA regime. This paper is based on an extensive bibliography on LSA, which includes official documents, academic papers, position papers and reports. Given the shift of spectrum policy focus from static to dynamic efficiency, the aim of this paper is to provide a preliminary assessment of the impact of LSA on dynamic efficiency. In this regard, selected elements of the LSA regime are assessed in terms of potential contribution to dynamic efficiency. These elements are: contract length; sharing arrangements; assignment procedures for LSA licences; implementation of RRS technologies; monitoring and enforcement. The preliminary assessment presented in this paper shows that the LSA regime needs to be refined to ensure that dynamic efficiency is promoted, in particular aspects of enforcement have to be carefully designed. The authors of this paper would recommend further studies on the LSA regime, which could represent a valuable element of the regulatory toolkit for spectrum management under a radio spectrum regulation aimed at increasing dynamic efficiency. The authors share the idea that different regimes can coexist and be applied depending upon spectrum bands and radio-based services under consideration.
Keywords: 330; Licensed Shared Access; spectrum sharing; static efficiency; dynamic efficiency